2016
DOI: 10.1111/mec.13565
|View full text |Cite
|
Sign up to set email alerts
|

Role of selection and gene flow in population differentiation at the edge vs. interior of the species range differing in climatic conditions

Abstract: Evaluating the relative importance of neutral and adaptive processes as determinants of population differentiation across environments is a central theme of evolutionary biology. We applied the QST-FST comparison flanked by a direct test for local adaptation to infer the role of climate-driven selection and gene flow in population differentiation of an annual grass Avena sterilis in two distinct parts of the species range, edge and interior, which represent two globally different climates, desert and Mediterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 107 publications
(160 reference statements)
0
9
0
Order By: Relevance
“…Several studies on different organisms (e.g. refs 31,41, 42, 43) have shown that peripheral populations that are migration-dependent may exhibit lower diversity and smaller population sizes than core populations. Therefore, migration-dependent peripheral populations have been shown to be more vulnerable to the detrimental effects of genetic drift (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on different organisms (e.g. refs 31,41, 42, 43) have shown that peripheral populations that are migration-dependent may exhibit lower diversity and smaller population sizes than core populations. Therefore, migration-dependent peripheral populations have been shown to be more vulnerable to the detrimental effects of genetic drift (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite markers are proven appropriate for population structure and differentiation studies (Pálsson 2000; Song et al 2006; Tyagi et al 2016; Volis et al 2016) and for investigating the relationship among closely related taxa (Korpelainen et al 2010; Talve et al 2013, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…As population genetic diversity is expected to be high in the centre and to decline at the margins of distribution ranges (Volis et al 2016), we studied the taxa neither in the centre nor the margins of theirs. Our southernmost population was at the latitude of 45.96 N in Caslano, Switzerland (V36), and the northernmost one at 59.29 N in Anija, Estonia (CF13).…”
Section: Methodsmentioning
confidence: 99%
“…) and it is not uncommon to detect local adaptation to the abiotic environment despite ongoing gene flow in natural populations (e.g., Kittelson and Maron ; Volis et al. ). Instead, it appears that in our study system the distance to other populations and isolation protect herbivore population from the negative effects of gene flow and migrants that can confound local adaptation in the more central populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some theoretical models predict that gene flow at low frequencies should promote local adaptation in host-enemy interactions (Gandon et al 1996;Gomulkiewicz et al 2000;Blanquart et al 2012). Studies with bacteriophages and their host bacteria verify that gene flow increases local adaptation in experimental coevolving populations (Brockhurst et al 2003;Forde et al 2004;Morgan et al 2005) and it is not uncommon to detect local adaptation to the abiotic environment despite ongoing gene flow in natural populations (e.g., Kittelson and Maron 2001;Volis et al 2016). Instead, it appears that in our study system the distance to other populations and isolation protect herbivore population from the negative effects of gene flow and migrants that can confound local adaptation in the more central populations.…”
Section: Discussionmentioning
confidence: 99%